Mental stress and well-being among low-income older adults during COVID-19 pandemic - Paolo Miguel Manalang Vicerra (Wolters Kluwer Medknow Publications, 2022)
Introduction: Insecurities with food and economic resources, housing discontent, and mental stress were experienced by vulnerable populations, especially older adults, during the COVID-19 pandemic. Methods: This study examined the association of poverty based on resource scarcity with life satisfaction as an indicator of well-being during the COVID-19 outbreak in Thailand. It also tested the mediating effect of mental stress. Structural equation modeling was used to analyze data from the 2021 Survey on Housing and Support Services for Poor Older Adults which involved low-income Thais aged at least 55 years. On testing for multigroup differences, the model was applied separately to urban and rural samples. Results: Findings from the urban sample indicated that resource scarcity was associated with life satisfaction based on the direct (β = 0.686, P < 0.01), indirect (β = 0.105, P < 0.05), and total effects (β = 0.790, P < 0.001). Mental stress (β = 0.304, P < 0.05) was also associated with life satisfaction. For the rural sample, resource scarcity was associated with life satisfaction (β = 0.159, P < 0.05) only when mental stress acted as a mediator. Conclusion: This theme is important to better understand the well-being status of older people in an aging society with a developing economy. Recognizing that the physical and policy environment for urban and rural residences have an influence on the mental health and well-being of this age group can contribute to addressing their needs in times of social shocks like the COVID-19 pandemic.